Interferometry of ionospheric E-region irregularities based on Kunming VHF radars - Chen, Bo; Xu, Yihao; Zhou, Chen; Zhang, Yuqiang; Liu, Yi; Xu, Tong; Xu, Bin; Feng, Jian; Lan, Ting; Qing, Haiyin; Deng, Zhongxin; Wang, Xiang; et al. (Frontiers in Astronomy and Space Sciences, 2024)
There is a long history of using VHF radar systems to detect ionospheric irregularities based on the theory of coherent scattering. According to previous work, there is a high occurrence of field-aligned irregularities (FAIs) in the ionospheric E-region over Kunming, China. In this paper, the VHF coherent scattering radar at Kunming is used to study the FAIs in the ionospheric E-region. Different arrangement of VHF radar antenna arrays, interferometry, and FAI echo parameter inversion methods are designed and tested. The measurement results show that the temporal and spatial characteristics of the irregularities can be obtained using these methods, as well as more refined spatial three-dimensional structure information. It is indicated that the new arrangement of the VHF radar antenna array is feasible to operate interferometry detection of E-region FAIs with the Kunming VHF radar.